Dramatic change in viscosities of pure ionic liquids upon addition of molecular solvents - Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2009)
Viscosities of binary mixtures of pyridinium based ionic liquids (1-butyl pyridinium tetrafluoroborate, [BP][BF(4)], 1-butyl 3-methyl pyridinium tetrafluoroborate [3-MBP][BF(4)], 1-butyl 4-methyl pyridinium tetrafluoroborate, [4-MBP][BF(4)]), and phosphonium based ionic liquids, (tetrabutyl phosphonium alaninate, [TBP][Ala]; tetrabutyl phosphonium valinate, [TBP][Val]) with the molecular solvents, water, methanol and dichloromethane, have been measured at 298.15 K. A Brookfield ultra-rheometer was employed to measure the reported viscosities. The drop in viscosity in the close vicinity of pure ionic liquid is more prominent in polar solvents like water compared to less polar solvents. The temperature dependence of this observation was also studied for binary mixtures of [4-MBP][BF(4)] with water in range of 298.15-323.15 K. The Vogel-Fulcher-Tamman (VFT) equation was employed to investigate the temperature dependence of the viscosities of pure pyridinium-based ionic liquids in the temperature range from 298.15-323.15 K.
Keywords: ionic liquids; Molecular solvents; VFT equations; viscosity